Optimizing the Raman signal for characterizing organic samples: The effect of slit aperture and exposure time. Issue 2 (2009) - Lázaro Lázaro, João Carlos João Carlos; Pacheco Pacheco, Marcos Tadeu T. Marcos Tadeu T.; Rodrigues Rodrigues, Kátia Calligaris Kátia Calligaris; de Lima de Lima, Carlos José Carlos José; Moreira Moreira, Leonardo Marmo Leonardo Marmo; Villaverde Villaverde, Antonio Balbin Antonio Balbin; Silveira Jr. Silveira Jr., Landulfo Landulfo
Abstract : The present work is focused on the influence of the slit aperture and time exposure of the infrared light on the Charge Coupled Device (CCD) in relation to their physical effects, in order to improve the Raman spectrum characteristics. Indeed, the alterations in slit aperture and CCD time exposure affect significantly important spectral properties, such as the spectral intensity, Signal to Noise Ratio (SNR) and band width resolution of the Raman spectra. Therefore, the present proposal has the aim of to found the optimum conditions of instrumental arrangement, involving the minimum collection time and maximum signal quality in dispersive Raman spectrometers. Samples of dehydrated human teeth and naphthalene were evaluated with a Raman dispersive spectrometer employing excitation wavelength of 830 nm in several integration times and spectrometer slit apertures. The analysis of the spectral intensity, SNR and band width of selected Raman peaks allowed to infer that these properties of a dispersive Raman spectrum depend directly of the exposure time on the detector as well as spectrograph slit aperture. It is important to register that the higher SNR was obtained with higher exposure time intervals. To the samples evaluated in the present article, the band width has lower values for slit apertures of 100–150 μm, i.e., in this aperture range the spectral resolution is maximum. On the other hand, the intensity and SNR of the Raman spectra becomes optimal for slit apertures of 150–200 μm, since this aperture does not affect significantly the integrity of the Raman signal. In this way, we can to propose that in approximately 150 μm, it is possible to obtain an optimum condition, involving spectral resolution as well as SNR and spectral intensity. In any case, depending of the priorities of each spectral measurement, the instrumental conditions can be altered according with the necessities of each specific chemical analysis involving a determined sample. The present data are discussed in details in agreement with recent data from literature.